2011
DOI: 10.1002/etc.1700
|View full text |Cite
|
Sign up to set email alerts
|

High polybrominated diphenyl ether levels in California house cats: House dust a primary source?

Abstract: Polybrominated diphenyl ethers (PBDEs) are brominated flame retardants that act as endocrine disruptors, affecting thyroid hormone homeostasis. As a follow-up to a recent study showing high PBDE levels in household cats and linking PBDE levels with cat hyperthyroidism, we measured PBDEs, polychlorinated biphenyls (PCBs), and organochlorinated pesticides (OCPs) in serum samples from 26 California household cats (16 hyperthyroid, 10 controls) using liquid-liquid extraction and high-resolution gas chromatography/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
84
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(91 citation statements)
references
References 36 publications
6
84
1
Order By: Relevance
“…This finding suggests differences in the exposure sources or in the uptake and metabolic efficiencies for the PBDE congeners among three species. The PBDE congener pattern in cats was similar to that of US cats where BDE 99 was also the major PBDE congener (Dye et al, 2007;Environmental Working Group, EWG, 2008;Guo et al, 2012). Other congeners, e.g.…”
Section: Levels Of Ohcs In Cat and Dog Serumsupporting
confidence: 50%
See 1 more Smart Citation
“…This finding suggests differences in the exposure sources or in the uptake and metabolic efficiencies for the PBDE congeners among three species. The PBDE congener pattern in cats was similar to that of US cats where BDE 99 was also the major PBDE congener (Dye et al, 2007;Environmental Working Group, EWG, 2008;Guo et al, 2012). Other congeners, e.g.…”
Section: Levels Of Ohcs In Cat and Dog Serumsupporting
confidence: 50%
“…Recent studies have suggested that they may serve as biosentinels of human exposure to various indoor contaminants (Environmental Working Group, EWG, 2008;Guo et al, 2012;Venier and Hites, 2011). Studies have documented that serum levels of polybrominated diphenyl ethers (PBDEs) were 20 to 100 fold higher in pet cats than the median levels in US adults (Dye et al, 2007;Environmental Working Group, EWG, 2008;Guo et al, 2012). However, scarce information is available on the contamination status of other OHCs, such as PCB and their metabolites, OCPs, novel BFRs (NBFRs) and bromophenols (BPs) in pets.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the polyphenolic compound bisphenol A, which is used as a plasticizer in can linings, has been detected in canned cat food and may act as a thyroid disruptor (Edinboro et al 2004, Schecter et al 2010. In a similar vein, recent studies both in the USA and Sweden have reported high levels of polybrominated diphenyl ethers (PBDEs) in cats, a fire-retardant with known thyroid-disrupting properties (Dye et al 2007, Guo et al 2012, Mensching et al 2012, Norrgran et al 2012. As PBDEs migrate out of the flame-protected materials (e.g.…”
Section: Why Has Feline Nodular Goiter Reached Such Epidemic Proportimentioning
confidence: 99%
“…plastics, textiles, furniture, or electronics), these chemicals end up in house dust as the natural sink (Suzuki et al 2008). Therefore, in addition to dietary sources of PBDEs, domestic cats living indoors and lying on the floor will normally collect dust in their fur and ingest these dust-enriched chemicals through grooming (Guo et al 2012, Johnson et al 2013. In the study of PBDEs and other endocrine-disrupting compounds, human beings and domestic cats share the same environments and tend to be chronically exposed to same chemical disruptors; however, because of their shorter life spans, companion animals may serve as good sentinels for human disease.…”
Section: Why Has Feline Nodular Goiter Reached Such Epidemic Proportimentioning
confidence: 99%
“…The sources of contaminants in household dust can be from the outdoor sources listed above or indoor sources resulting from activities (e.g., smoking, pets in the home) or chemicals and products used in the home (e.g., new carpets, and sofas, pesticides, cleaning products) (Guo et al, 2012;Hwang et al, 2008;Thorne, Cohn, May, Arbes, & Zeldin, 2009). …”
Section: Introductionmentioning
confidence: 99%